Persistent Thrombocytopenia Post Autologous Transplant In A Case Of Extra Nodal Nk Cell Lymphoma - K. Goel, Dr. Deepak; Sabina Langer; Jyoti Kotwal; Amrita Saraf; Pallavi Prakhar (Tropical Journal of Pathology and Microbiology, 2024)
Natural killer (NK)-cell lymphomas are a rare type of lymphoid malignancy with predominantly extranodal nasal involvement leading to destruction of midline head and neck structures. This article presents a case of extranodal nasal type NK cell lymphoma which even after aggressive treatment relapsed in leukemic form with no evidence of lesion at the primary site or any solid organ. This case report aims to highlight the importance of careful peripheral smear examination, knowledge of flow cytometry in early and accurate diagnosis of leukemic spillover of this rare entity and the need for aggressive treatment.